(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Theearly poetry of this century explored decadence and breakdown of values in bothculture and individuals. At least this could be argued as a central drivingforce in the Eliot of ’The Waste Land and Other Poems’, of Pound’s cantos andin parts of Yeats. But in these poets there remains this assumption that theywere writing not just of their own sense of a crisis of values, but of thatshared by a whole society, and they wrote from the position of a strong andauthoritative sense of their own purposeful identity.